Personalized approaches for treatment-naïve mantle cell lymphoma. Issue 2 (1st February 2023) - Qualls, David; Kumar, Anita
ABSTRACT: Introduction: Mantle cell lymphoma (MCL) can have diverse disease presentations, which vary in aggressiveness and prognosis, and can occur in patients with varying ability to tolerate therapy. Additionally, the options for treatment of MCL have expanded rapidly in the last decade, translating to improved outcome for patients. Areas covered: We review the initial evaluation of patients with MCL, identifying disease- and patient-specific prognostic factors, along with personalized therapies for patients with MCL. Specific scenarios include indolent and limited-stage MCL, advanced-stage disease in transplant-eligible and ineligible patients, and high-risk TP53 mutant disease. Ongoing trials and future directions in MCL treatment are also highlighted. Expert opinion: Given the wide array of disease and patient presentations with MCL, a personalized therapeutic approach is needed to optimize outcomes. The best therapeutic strategy should incorporate disease prognostic factors, patient status and comorbidities, goals of care, and response to treatment.